Ice formation, growth and associated substrate supply determine sea-ice bacterial community dynamics - Eronen-Rasimus, Eeva (Helsingin yliopisto, 2015)
Sea ice, at its maximum extent, is one of the largest biomes on Earth. In addition to the polar oceans, it covers extensive sea areas at lower latitudes such as the Baltic Sea and the Sea of Okhotsk. During ice formation, organic and inorganic components in the parent seawater are concentrated into saline brines within the ice, which serve as a habitat for diverse auto- and heterotrophic organisms, including bacteria. Sea-ice bacteria are responsible for many biogeochemical processes, such as decomposition of particulate organic matter, recycling of dissolved organic matter and remineralization of nutrients, analogously to bacterially driven biogeochemical processes in the water column. Since bacterial groups vary by their metabolic traits and participation in biogeochemical processes, knowledge of the bacterial community structure and its seasonal variation is essential for an understanding of ice biogeochemistry. This thesis characterises sea-ice bacterial communities during ice formation and during the winter/spring transition phase when the community composition is poorly known. Bacterial communities in Arctic and Baltic sea ice during the winter/spring transition were studied and compared. In addition, the effect of the dissolved organic matter regime on bacterial community formation was investigated in an experimental sea-ice system with North Sea water. The main methods applied were terminal-restriction fragment length polymorphism and/or Illumina Miseq sequencing together with bacterial production and abundance measurements. During the early stages of sea-ice formation, the bacterial communities were similar to the parent water communities, suggesting that the parent water determines the initial sea-ice bacterial community composition. After congealment of the sea ice, the bacterial communities changed towards communities typical of sea ice in spring. During the winter/spring transition, members of the classes Flavobacteriia (formerly Flavobacteria), Gammaproteobacteria and Alphaproteobacteria were ...